Involvement of Innate Immune Receptors in the Resolution of Acute Hepatitis B in Woodchucks - Suresh, Manasa; Li, Bin; Murreddu, Marta G.; Gudima, Severin O.; Menne, Stephan (Frontiers in Immunology, 2021)
The antiviral property of small agonist compounds activating pattern recognition receptors (PRRs), including toll-like and RIG-I receptors, have been preclinically evaluated and are currently tested in clinical trials against chronic hepatitis B (CHB). The involvement of other PRRs in modulating hepatitis B virus infection is less known. Thus, woodchucks with resolving acute hepatitis B (AHB) after infection with woodchuck hepatitis virus (WHV) were characterized as animals with normal or delayed resolution based on their kinetics of viremia and antigenemia, and the presence and expression of various PRRs were determined in both outcomes. While PRR expression was unchanged immediately after infection, most receptors were strongly upregulated during resolution in liver but not in blood. Besides well-known PRRs, including TLR7/8/9 and RIG-I, other less-characterized receptors, such as IFI16, ZBP1/DAI, AIM2, and NLRP3, displayed comparable or even higher expression. Compared to normal resolution, a 3–4-week lag in peak receptor expression and WHV-specific B- and T-cell responses were noted during delayed resolution. This suggested that PRR upregulation in woodchuck liver occurs when the mounting WHV replication reaches a certain level, and that multiple receptors are involved in the subsequent induction of antiviral immune responses. Liver enzyme elevations occurred early during normal resolution, indicating a faster induction of cytolytic mechanisms than in delayed resolution, and correlated with an increased expression of NK-cell and CD8 markers and cytolytic effector molecules. The peak liver enzyme level, however, was lower during delayed resolution, but hepatic inflammation was more pronounced and associated with a higher expression of cytolytic markers. Further comparison of PRR expression revealed that most receptors were significantly reduced in woodchucks with CHB, and several RNA sensors more so than DNA sensors. This correlated with a lower expression of receptor adaptor and effector molecules, suggesting that persistent, high-level WHV replication interferes with PRR activation and is associated with a diminished antiviral immunity based on the reduced expression of immune cell markers, and absent WHV-specific B- and T-cell responses. Overall, the differential expression of PRRs during resolution and persistence of WHV infection emphasizes their importance in the ultimate viral control during AHB that is impaired during CHB.